Implementation of e-government in Poland with the example of the Silesian Voivodeship - Ziemba, Ewa; Papaj, Tomasz (Wdrożenie e-government w Polsce na przykładzie województwa śląskiego, 2012)
The aim of this paper is to explore the concept of e-government as well as to present the implementation of e‑government in the Silesian Voivodship, Poland. The structure of the paper is subordinated to this aim. Firstly , the essence of e-government has been described and the initiatives for building e-government in Poland have been identified. Particular attention was paid to the Electronic Communication System for Public Administration (SEKAP) and the diagnosis of SEKAP implementation is given. Finally, the barriers and critical success factors for SEKAP implementation have been indentified. The achieved results can be useful whilst undertaking activities aimed at e‑government development in a country and particular regions
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 207-221
Keywords: e-government; e-government services; e-government implementation; CSFs for the e-government; G2G; SEKAP; e-administracja; e-usługi publiczne; wdrożenie administracji; krytyczne czynniki sukcesu e-administracji